2010
DOI: 10.1007/s11033-010-9957-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of the colorectal cancer and MDR1 gene polymorphism in an Iranian population

Abstract: The human multidrug resistance (MDR1) gene product P-glycoprotein is highly expressed in intestinal epithelial cells, where it constitutes a barrier against xenobiotics, bacterial toxins, drugs and other biologically active compounds, possibly carcinogens. In this study, an association of MDR1 gene polymorphism and the occurrence of colorectal cancer were evaluated. In this case-control-designed 118 unrelated colorectal cancer and 137 sex-and-ages matched healthy controls were enrolled. The C3435T MDR1 gene po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
1
8
2
1
Order By: Relevance
“…This was inconsistent with most other studies [13][14][15][16][17][18][19][20][21][22]. In this meta-analysis the results when stratified for ethnicity or population source, indicated no association between ABCB1 rs1045642 SNPs and CRC.…”
Section: Discussioncontrasting
confidence: 98%
“…This was inconsistent with most other studies [13][14][15][16][17][18][19][20][21][22]. In this meta-analysis the results when stratified for ethnicity or population source, indicated no association between ABCB1 rs1045642 SNPs and CRC.…”
Section: Discussioncontrasting
confidence: 98%
“…In agreement with our results, Andersen and co-workers found that carriers of C allele of the C3435T polymorphism had an increased risk of CRC in Norwegian Caucasian population (Andersen et al, 2009). On the contrary, in an Iran population investigation, T allele of the ABCB1 C3435T polymorphism showed significantly increased risk of CRC (Khedri et al, 2011), while others did not find any statistically significant associations (Bae et al, 2006;Samanian et al, 2011). Regarding ABCB1 G2677T/A genotypes and risk for CRC, we did not find any correlation between CRC risk and the investigated G2677T/A genotypes, likewise, De Iudicibus et al found no relation between ABCB1 G2677T/A polymorphism and CRC patients (De Iudicibus et al, 2008).These data suggest that the role of the ABCB1 polymorphisms in cancer risk may vary with ethnicity, a possibility that warrants further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…Overall these studies are heterogeneous in terms of size, number of SNPs tested, methodology used and ethnicity. C3435T was found to be associated with disease risk in several case-control studies [33], [57], [58], [59] while others did not find any statistically significant associations [34], [60] The polymorphism variant 2677G>T/A (rs2032582) in exon 21 has also been found associated with CRC risk [26], [45], [59], although not in all studies [34]. Anderson and colleagues also tested the possible association of rs3789243 in two distinct studies.…”
Section: Discussionmentioning
confidence: 99%